Clinico-Radiological Characteristics and Predictors of Poor Outcome of Cerebral Venous Sinus Thrombosis - Hassan, Kamrul; Md. Hassanuzzaman; Touhidur Rahman; Fatama-Tuz-zannat Puspa; Samee M Adnan; Shagor Deb Tapu; Md. Mubinul Huq Chowdhury; Aditi Das (Bangladesh Journal of Neuroscience, 2026)
Background: Cerebral venous sinus thrombosis (CVST) is an acute cerebrovascular disease diagnosed more frequently nowadays. Though most patients with CVST have independent survival in the short term, a small percentage have an unfavorable outcome and remain dependent functionally. Objective: This study aimed to explore the clinical profiles, radiological features, risk factors and outcomes of patients with CVST in a tertiary-level hospital in Bangladesh with a special emphasis on determining the factors influencing the clinical outcome. Materials and Methods: This prospective analytical study included 40 patients confirmed to have CVST clinically and radiologically. Followup information included the modified Rankin Scale (mRS) at discharge and 90 days of follow-up from the diagnosis. Results: The mean age was 33±10.7 years, and 67.5% were female. Female-specific risk factors (Oral contraceptive pill use and pregnancy) were more common in the study, followed by infections, hematological conditions, smoking, prothrombotic conditions, and malignancy. Common symptoms/signs were dull aching bilateral headache, vomiting, focal or bilateral tonic-clonic seizure, limb weakness, visual disturbance, altered mental status and papilledema. On MRI, hemorrhagic and non-hemorrhagic infarct was observed respectively, in 28 (70%) and 3 (7.5%) patients. Parenchymal lesions were found in 31 (77.5%) patients. Most patients had superficial sinus involvement, and superior sagittal sinus, transverse sinus, and sigmoid sinuses were the frequently affected sinus. Twenty-two (55%) patients had poor outcomes (mRS > 2) at discharge and 5 (12.5%) at 90 days with a mortality rate of 7.5%. Most of the patients (87.5%) had good functional outcomes at 90 days. The presence of limb weakness and multiple risk factors were related to the outcome. On multivariate analysis, the number of total risk factors (OR = 10.43; 95% CI = 1.02-12.95; p=0.048) predicted the outcome at 90 days. Conclusions: CVST represents a relatively benign disease. However, CVST may result in an unfavorable outcome, particularly in patients with more than one risk factor at presentation.